Multivariate analysis of trace metals in industrial and domestic effluent by inductive couple plasma mass spectroscopy (ICP-MS) - Abdul Rais, Nazifa; Abdullah, Shakila; Khamidun, Mohd Hairul (Penerbit UTHM, 2020)
Heavy metals in industrial and domestic wastewater represent a major environmental problem and are potentially harmful to both human and animal. In this study, the concentrations of heavy metals were determined in various types of wastewater such as food, textile and domestic. Wastewaters were collected from three different sampling locations which is food industry, textile industry and domestic located at Batu Pahat, Johor. The samples were analyzed based on physicochemical parameter (COD, BOD, DO, colour, pH, temperature, TOC, TSS, NH3-N), heavy metals (Ni, Cu, Cd, Pb, Mn) and radionuclides (Uranium) using standard methods for Examination of water and wastewater and ICP-MS respectively. The concentration of all physicochemical properties, heavy metals and radionuclides are below the permissible limit set by DOE except for pH value, colour, TSS, NH3-N, COD, TOC along with heavy metal Cd. However, this study would provide a safe disposal of the effluents to the environment against elevated level of the toxic contaminants.